Brykov M.N., Prokopchenko A.A., Efremenko V.G. Effect of quenching and isothermal processing conditions on the structure and wear resistance of high-carbon low-alloy steel. - Брыков, М.Н.; Прокопченко, А.А.; Ефременко, В.Г. (Problems of Tribology, 2016)
The aim of the research presented was the heat treatment optimization of 120Mn3Si2 steel on a "quenching + isothermal holding" process. Investigated are the structure, hardness and wear resistance of this steel after quenching from different temperatures in the range 760 ... 1000 ° C followed by isothermal holding at 250 ° C. It is found that after quenching from 900 °C the rate of bainite transformation is maximal. Hardness of samples reaches the level of 500 HV within 1 day during isothermal holding, and changed insignificantly at subsequent treatment. As a result of this treatment the martensite-austenite-bainite structure with little or no carbide phase is formed. Attention is drawn to the almost complete absence of excess carbides. Only a few remnants of undissolved carbide phase are visible in the structure. The wear resistance of steel after optimal treatment is much higher than the wear resistance of the martensite.Further work may be aimed at the study of the mechanical properties of 120Mn3Si2 steel after this treatment, as well as ways for its practical use. Also of interest are the tests of 120G3S2 after a similar treatment in the mixed conditions of abrasive wear with the simultaneous impact of low-cycle and high-cycle fatigue of the friction surface.Keywords: abrasive wear, steel, isothermal treatment, bainite, wear resistance.